Effects of Ovarian Transplant on Anti-Mullerian Hormone, Kisspeptin-1, and Kisspeptin-1 Receptor Levels in Rats - Risvanli, Ali; Ocal, Halis; Timurkaan, Necati; Ipek, Pinar; Cevik, Aydin; Seker, Ibrahim (Baskent Univ, 2020)
Objectives: Information is scarce on levels of kisspeptin-1 and the kisspeptin-1 receptor in females after ovarian transplant. In this study, our aim was to explore serum estradiol, anti-Mullerian hormone, kisspeptin-1, and kisspeptin receptor levels, along with kisspeptin-1-positive cell density, in ovaries from rats after ovarian transplant. Materials and Methods: For this study, 28 female Sprague Dawley rats were divided into 4 groups, with sham surgery performed on rats in group 1 (control group). Group 2 rats had ovaries transplanted under the peritoneum, and group 3 rats had their own ovaries transplanted subcutaneously. Group 4 rats were maintained in an estrous state. Serum antiMullerian hormone, kisspeptin-1, estradiol, and ovarian kisspeptin receptor levels were determined using commercial enzyme-linked immunosorbent assay kits. Kisspeptin-1-positive cell densities in the ovaries were determined immunohistochemically.The ovaries were also examined histopathologically. Results: Our statistical analyses showed that levels of kisspeptin receptors in the ovaries were lowest in the subcutaneously transplanted group (group 3; 628.57 +/- 35.69 pg/mL). The highest serum antiMullerian hormone levels were found in the estrous group (group 4; 16.91 +/- 2.12 ng/mL). Differences between groups in terms of serum kisspeptin-1 and estradiol concentrations were not statistically significant. Conclusions: Our findings suggest that, in rats, results were better in the peritoneum transplant group than in the subcutaneous transplant group. We also found that serum anti-Mullerian hormone levels were lower in the transplant groups than in the estrous group, although levels were not completely decreased to zero. These results support the finding that ovarian activities continue after transplant.
Keywords: Animal model; Estradiol; Infertility